An efficient algorithm for text encryption on android devices (International Journal of Engineering and Computer Science, 2024)
In the era of digital communication, ensuring the confidentiality and integrity of sensitive information is paramount. This dissertation introduces a robust text encryption system that combines the strengths of Advanced Encryption Standard (AES) and Rivest-Shamir-Adleman (RSA) algorithms to create a hybrid encryption approach. Object Oriented Design (OOD) was used for the design methodology. The proposed system leverages the efficiency of AES for symmetric key encryption and the security benefits of RSA for key exchange and digital signatures. The encryption process begins with the generation of a random symmetric key for each communication session, which is then used for the AES encryption of the plaintext. The symmetric key is subsequently encrypted using the recipient's RSA public key, ensuring secure key exchange. This hybrid approach harnesses the speed of AES for bulk data encryption while utilizing RSA's asymmetric encryption for the secure sharing of secret keys. The system incorporates digital signatures generated using RSA to authenticate the sender and verify the integrity of the encrypted message. This dual-layered encryption strategy not only safeguards the confidentiality of the message but also provides assurance of the message origin and integrity. The implementation of this hybrid AES-RSA encryption system using Python programming language offers a versatile solution suitable for diverse communication channels, including email, messaging platforms, and file transfers. Its robustness against common cryptographic attacks makes it an ideal choice for securing sensitive information in various applications, such as financial transactions, healthcare communication, and government data exchange. The experimental results demonstrate the efficacy of the proposed system, with significantly reduced encryption and decryption times—0.5005 seconds and 0.5003 seconds, respectively—when compared to existing systems. This noteworthy improvement in processing speed enhances the system's practical applicability for real-time communication scenarios.